On Minimum Eigenvalue for the Fan Product of Matrices - H.K. Patel, Leena Sharma, V.H. Badshah (International Journal of Advanced Science and Technology, 2020)
For two non negative matrices  and , we introduced a new lower limit or bound for the minimum eigen value of the Fan product of  and . Using the result of Huang [5], we establish this new lower bound. Calculation of this new bound is easy, because it depends only on the elements of matrices.